Spirituality, theology and the critical mind - P. G. R. de Villiers (Acta Theologica)
This essay investigates aspects of the critical nature of spirituality as a discipline. It first analyses how a recent publication on philosophy critiques the role of the critical mind in contemporary  philosophy and how it reclaims spirituality as solution for what went wrong. In a next section it discusses similar criticism of traditional theology and spirituality by Contextual Theologies and points out the development of Contextual Spiritualities as a critical response and solution to what went wrong. It finally focuses on the selfimplicating nature of the critical mind in terms of the spirituality of the researcher as a safeguard against such excesses and against the deformation of the critical mind.